THE EFFECT OF TRUST IN STREAMERS ON LIVE SHOPPING CONSUMERS' PURCHASE INTENTION IN INDONESIA - Wijaya, Yitlin; Manaf, Peri A. (Unitri Press, 2024)
This study aims to analyze the effect of trust in streamers on live shopping consumers’ purchase intention in Indonesia. Data collection was obtained from 150 respondents through an online questionnaire and used a structural equation modeling method with SmartPLS 4.0 data processing. The results of hypothesis testing show that utilitarian value, hedonic value, and value similarity are proven to have a significant positive effect on trust in streamers, while trust in streamers is also proven to have a significant positive effect on purchase intention. Meanwhile, trust in streamers is not proven to have a negative relationship with product fit uncertainty and product quality uncertainty even though they have a significant effect while product fit uncertainty and product quality uncertainty are proven to not affect purchase intention. This finding has important managerial implications for live shopping business owners that the right price and product quality, fast delivery, and lower delivery service costs, as well as the comfort and pleasure that consumers get in live shopping, will increase the trust in streamers. Similar ways of thinking, similar tastes, and similar preferences between streamers and consumers also play an important role in increasing trust in streamers in live shopping. They are expected to be aware of the importance of factors that can build consumers’ trust in streamers because trust in streamers has been proven to increase consumers’ purchase intention.